Forming Mechanism of Political Risks in International Construction Projects: From the Perspective of Chinese Contractors - Ullah, Safi; Deng, Xiaopeng; Chang, Tengyuan (Frontiers in Built Environment, 2019)
The performance is analyzed from the perspective of the characteristics of overseas business of Chinese contractors and political risks. Based on the results of this research project, the funds and pricing model of Chinese Contractors Overseas Projects were further analyzed, as well as their ability to withstand political risks and coping strategies. The purpose of this study was to study the statistical analysis of risks in design systems and international activities within the framework of international construction projects. This research is based on one belt and one road. The questionnaire was distributed to 100 Chinese international contractors in the form of emails. Of the 100 contractors, 50 are in the top 225 of the 2017 ENR. Research was based on the projects, and for each project only a single questionnaire was filled in, for a total of 370 responses, and a recovery rate was 37%. Three hundred seventy respondents were from 46 Chinese international contractors, of which 28 (60.87%) are from top ENR225 enterprises and 18 (39.13%) are from other enterprises. This survey reflects the general situation of political risks of Chinese contractors in overseas project management. Generally speaking, Chinese contractors are facing higher political risks, and they do not attach enough importance to political risks, and their ability to deal with political risks. The study provides useful guidance on how to manage the political risks that international contractors create in this emerging market.